Nonlinear response of soil respiration to increasing nitrogen additions in a Tibetan alpine steppe - Yunfeng Peng; Fei Li; Guoying Zhou; Kai Fang; Dianye Zhang; Changbin Li; Guibiao Yang; Guanqin Wang; Jun Wang; Anwar Mohammat; Yuanhe Yang (Environmental Research Letters, 2017)
Nitrogen (N) availability is a key regulator of carbon (C) cycling in terrestrial ecosystems. Anthropogenic N input, such as N deposition and fertilization, increases N availability in soil, which has important implications for an ecosystem’s C storage and loss. Soil respiration (Rs), which is the second largest C flux from terrestrial ecosystems to the atmosphere, plays an important role in terrestrial C cycles. The direction and magnitude of the responses of Rs and its components to N addition have been widely evaluated, but it remains unclear how these processes change across multiple N addition levels. Here we conducted a two-year field experiment to examine the changes of Rs and its autotrophic respiration (Ra) and heterotrophic respiration (Rh) components along a gradient of eight N levels (0, 1 2, 4, 8, 16, 24, 32 g m ^−2 yr ^−1 ) in a Tibetan alpine steppe, and used structural equation modeling (SEM) to explore the relative contributions of biotic and abiotic variables and their direct and indirect pathways regulating the Ra and Rh. Our results indicated that both Rs and Ra exhibited first increasing and then subsequent decreasing trends at the threshold of 8 g N m ^−2 yr ^−1 . In contrast, the Rh declined linearly with the N addition rate continuously increasing. SEM analysis revealed that, among various environmental factors, soil temperature was the most important one modulating Rs, which not only had a direct effect on the two Rs components, but also indirectly regulated the Ra and Rh via root and microbial biomass. These findings suggest that the nonlinear response patterns of Rs should be considered for better predicting terrestrial C balance, given that anthropogenic N input to the terrestrial ecosystems is increasing continuously.